2020
DOI: 10.1042/bsr20194065
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of p53-dependent apoptosis signal in antitumor effect of Colchicine on human papilloma virus (HPV)-positive human cervical cancer cells

Abstract: Colchicine, a plant-derived alkaloid with relatively low toxicity on normal human epidermal keratinocytes (HEKn), has selective inhibitory effect on the growth of CaSki (HPV16-positive) and HeLa (HPV18-positive) human cervical cancer cell lines via the induction of apoptosis. Colchicine (2.5, 5.0 and 10.0 ng/ml) significantly reduced the expression of human papilloma virus (HPV) 16 E6/E7 mRNA and protein in CaSki and HeLa cells. Moreover, reduced expression of E6 and E7 induced by Colchicine resulted in the up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
(40 reference statements)
1
7
0
Order By: Relevance
“…The tumor suppressor gene TP53 is involved in tumor necrosis factor‐α (TNF‐α)‐mediated apoptosis by inducing cell cycle arrest, inhibiting cell proliferation, and ultimately leading to apoptosis. 39 In our experiments, an increase in p53 was also detected at both the transcriptional and translational levels. The above results once again confirmed the inhibitory effect of Nr‐CWS on cervical carcinoma cells.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The tumor suppressor gene TP53 is involved in tumor necrosis factor‐α (TNF‐α)‐mediated apoptosis by inducing cell cycle arrest, inhibiting cell proliferation, and ultimately leading to apoptosis. 39 In our experiments, an increase in p53 was also detected at both the transcriptional and translational levels. The above results once again confirmed the inhibitory effect of Nr‐CWS on cervical carcinoma cells.…”
Section: Discussionsupporting
confidence: 69%
“…In vivo and in vitro experiments have demonstrated that Nr‐CWS can reduce the expression levels of E6 and E7 oncoproteins in cervical carcinoma cells and tumor tissues. The tumor suppressor gene TP53 is involved in tumor necrosis factor‐α (TNF‐α)‐mediated apoptosis by inducing cell cycle arrest, inhibiting cell proliferation, and ultimately leading to apoptosis 39 . In our experiments, an increase in p53 was also detected at both the transcriptional and translational levels.…”
Section: Discussionmentioning
confidence: 49%
“…Colchicine, a plant-derived alkaloid, could significantly reduce the expression of HPV 16 E6/E7 mRNA and protein in CaSki and HeLa cells. This effect results in up-regulation of tumor suppressor proteins p53 and Rb and down-regulation of phosphorylated Rb (pRb) proteins (Yan et al, 2020).…”
Section: Alkaloidsmentioning
confidence: 99%
“…Furthermore, harmine induced apoptosis in breast cancer cells in a time-dependent manner and real-time PCR outcomes on breast cancer cells showed that apoptosis induction in MCF-7 cells by harmine requires the activation of p53 gene expression [ 185 ]. Colchicine exhibits in vitro antiproliferative activity against HPV 16/18-positive human cervical cancer cell lines, which was achieved by HPV E6/E7 inhibition and subsequently p53-dependent intrinsic apoptosis [ 186 ].…”
Section: P53 Signaling Pathway Modulated By Dietary Antioxidantsmentioning
confidence: 99%